The impact of pulmonary hypertension on prognosis in moderate-to-severe mitral regurgitation patients treated with transcatheter edge-to-edge mitral valve repair: a comprehensive meta-analysis - Wei, Zhili; Shao, Xinquan; An, Zhijing; Chang, Yixuan; Liu, Shidong; Luo, Ziran; Chen, Yang; Song, Bing (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis meta-analysis aims to assess the impact of pulmonary hypertension (PH) on the clinical prognosis of patients with moderate to severe mitral valve regurgitation (MR) undergoing transcatheter edge-to-edge mitral valve repair (TEER).MethodsAs of August 2024, relevant studies were identified through searches of the PubMed, Cochrane Library, Web of Science, and Embase databases. A comprehensive screening process was conducted, with quality assessment performed utilizing the Newcastle Ottawa Scale (NOS). Data analysis was carried out using Stata17.0 software, generating forest plots, funnel plots, Egger's test, and sensitivity analysis plots to analyze heterogeneity and publication bias. Odds ratios (OR) and standardized mean differences (SMD) were calculated for dichotomous and continuous variables, respectively, each presented with a 95% confidence interval (CI).ResultsA total of 10 studies involving 28,404 patients were included, with all articles achieving a NOS score of ≥7. The outcome indicators were as follows: 2-year all-cause mortality [OR = 2.06, 95%CI(1.49, 2.84), p < 0.01, I2 = 79.9%]; heart failure rehospitalization rate [OR = 1.56, 95%CI(1.29,1.76), p < 0.01, I2 = 41.7%]; 30-day all-cause mortality [OR = 2.10, 95%CI(1.78,2.47), p < 0.01, I2 = 0%]; cardiogenic mortality [OR = 2.00, 95%CI (1.61,2.49), p < 0.01, I2 = 0%]; and length of hospital stay [OR = 0.17, 95%CI(0.14,0.20), p < 0.01, I2 = 0%]. All outcome indicators demonstrated that the PH group had significantly worse outcomes compared to the non-PH group. Subgroup analyses were performed on outcome indicators with notable heterogeneity, focusing on PH measurement methods, PH diagnostic criteria, and the severity of PH. The results indicated that most combined subgroup outcomes were consistent with the overall findings and showed significantly reduced heterogeneity. The sources of heterogeneity are likely attributed to the methods of PH measurement, diagnostic criteria for PH, and the severity of PH.ConclusionWithin two years after undergoing transcatheter edge-to-edge repair (TEER), patients with MR and PH experiecne significantly higher rates of all-cause mortality, 30-day all-cause mortality, heart failure readmissions, cardiogenic mortality, and longer hospital stays compared to those without PH.Systematic Review Registrationhttps://inplasy.com/, identifier (INPLASY202480068).